Organoammonium Salt-Catalyzed Enantioselective Cycloaddition Reactions with α-(Acyloxy)- or α-Diacylaminoacroleins - Sakakura, Akira; Ishihara, Kazuaki (Bulletin of the Chemical Society of Japan, 2010)
The rational design of small-molecule chiral catalysts is an important subject in the development of practical organic syntheses. We have designed primary ammonium salt catalysts for enantioselective cycloaddition reactions with α-substituted acroleins such as α-(acyloxy)acroleins and α-diacylaminoacroleins. Ammonium salts of an aliphatic triamine derived from H–L-Phe–L-Leu–N(CH2CH2)2 successfully promote the Diels–Alder reaction of α-(acyloxy)acroleins and α-(N,N-diacylamino)acroleins, and the [2 + 2] cycloaddition reaction of α-(acyloxy)acroleins with high enantioselectivity. An ammonium salt of a C2-symmetric aromatic diamine, 1,1′-binaphthyl-2,2′-diamine, with a superacid is also an efficient catalyst and shows high activity and enantioselectivity for the Diels–Alder reaction of cyclic dienes with α-(acyloxy)acroleins.